2005
DOI: 10.1097/01.don.0000145422.94578.e6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apical Instrumentation in Root Canal Treatment: A Review of the Literature

Abstract: The issue of final apical preparation size remains controversial despite considerable clinical and in vitro research. The astute clinician must be aware of this research before choosing any instrumentation system because the informed clinician's decision must be guided by the best available evidenced-based information. This review article generated a Medline-based search strategy to disclose these studies and provides a critique and summary of the results.From the University of Pittsburgh School of Dental Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 92 publications
1
114
0
17
Order By: Relevance
“…One study has suggested that a large diameter at the coronal orifice and a gradual taper towards the apical constriction offers the ideal instrumentation technique for thermo-plasticized obturation 31) . Indeed, many instrumentation techniques have been designed with the obturation phase in mind, rather than achieving optimal chemomechanical debridement of the infected root canal systems 1) . Apical clearing (a) removes existing and created dentin chips and soft tissue debris compacted in the apical region; (b) permits deeper placement of an irrigation needle for more effective final irrigation; and (c) enlarges and produces a more uniform shape in the apical region in order to facilitate placement and fit of the master cone 12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has suggested that a large diameter at the coronal orifice and a gradual taper towards the apical constriction offers the ideal instrumentation technique for thermo-plasticized obturation 31) . Indeed, many instrumentation techniques have been designed with the obturation phase in mind, rather than achieving optimal chemomechanical debridement of the infected root canal systems 1) . Apical clearing (a) removes existing and created dentin chips and soft tissue debris compacted in the apical region; (b) permits deeper placement of an irrigation needle for more effective final irrigation; and (c) enlarges and produces a more uniform shape in the apical region in order to facilitate placement and fit of the master cone 12) .…”
Section: Discussionmentioning
confidence: 99%
“…However, such studies have often been retrospective or included confounding factors, which has rendered their results inconclusive 1) . One recent clinical study found a correlation between apical width and the success of root canal treatment; an improvement in outcome was observed with increase in apical enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is disagreement amongst endodontic specialists about the ideal apical diameter of root canal preparation, there is universal consensus that the ideal size depends on anatomical, microbiological, and mechanical factors 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…7,8) 따라서 치근단 3 mm 이내 지역인"critical zone"에서의 적절한 근관확대의 크기는 개개 치아의 근단공의 해부학적 형태와 직경 및 근관감염 정도를 토대로 신중하게 결정해야 한다. 9,10) How can we estimate the size of apical constriction as accurate as possible? …”
Section: 서 론unclassified